Reasons for requesting radiographs in an accident department. Issue 6178 (16th June 1979) - de Lacey, G; Barker, A; Wignall, B; Reidy, J; Harper, J
Abstract : A prospective study of 500 patients was performed to determine the reasons for requesting radiographs in an accident and emergency department. Most examinations were requested either to confirm a clinically suspected abnormality or because of difficulty in excluding a significant bone injury on clinical grounds alone. Several requests were also made to reassure the patient. Medicolegal reasons were relatively few, and those made purely because the doctor feared litigation probably accounted for only 5% of requests. Undue emphasis on the medicolegal aspects of accident and emergency radiography in the United Kingdom is unhelpful in that it directs attention away from the real reasons for x-ray referral. Although a reduction in the number of x-ray examinations is desirable on the grounds of expense and radiation exposure it is likely to be obtained only by improving experience and acumen in the clinical assessment of injuries.